2011
DOI: 10.1002/ibd.21625
|View full text |Cite
|
Sign up to set email alerts
|

Altered O-glycosylation profile of MUC2 mucin occurs in active ulcerative colitis and is associated with increased inflammation

Abstract: In the majority of the active UC patients MUC2 mucin has an altered glycan profile as compared to inactive UC and control patients. Patients with strong alterations in the glycan pattern tended to have a more severe disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(239 citation statements)
references
References 48 publications
5
218
0
3
Order By: Relevance
“…Muc2 is a heavily O-glycosylated mucin, and the impact of its glycosylation was noted by a recent study examining different glycosylation patterns of Muc2 in mice and humans (49,50). In agreement with previous findings (13), we found that core 3 O-glycosylation plays a major role in protecting intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Muc2 is a heavily O-glycosylated mucin, and the impact of its glycosylation was noted by a recent study examining different glycosylation patterns of Muc2 in mice and humans (49,50). In agreement with previous findings (13), we found that core 3 O-glycosylation plays a major role in protecting intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus is impermeable to commensal bacteria, with the exception of that forming the outer layer in the colon (Johansson et al, , 2008(Johansson et al, , 2013. Mucins are highly glycosylated proteins produced and released by goblet cells that vary in structure, function and sites of expression (Fu et al, 2011;Johansson et al, 2013;Larsson et al, 2011;Sommer et al, 2014). For example, differences in their protein domains distinguish the transmembrane mucins anchored to the epithelial layer from the detached gel-forming mucins.…”
Section: Mucin Is An Extracellular Component Essential In Barrier Funmentioning
confidence: 99%
“…These glycan chains are highly heterogeneous in chain length and composition even at homeostasis. Importantly, glycan structure can be influenced during parasitic infections, which aids host protection against pathogenesis (which will be discussed further below) 33, 34, 35, 36…”
Section: Muc2 Biosynthesismentioning
confidence: 99%